PENYULUHAN DAN PELATIHAN BIDANG KESEHATAN KADER POSBINDU - PTM DESA SUMBERWONO DI MASA PANDEMI COVID-19 - Yudha Laga Hadi Kusuma; Dwiharini Puspitaningsih (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
One of the efforts to control non-communicable diseases through Posbindu-PTM must be carried out on an ongoing basis. During the COVID-19 pandemic, these efforts need to be continued by providing the counseling and training the newest issues to health cadres on the application of health protocols when implementing Posbindu-PTM. The purpose of community service carried out by the STIKES Majapahit lecturer team is to increase the knowledge and skills of cadres in implementing Posbindu-PTM during the COVID-19 pandemic by implementing health protocols. This community service activity is carried out using the PLA or Participatory Learning and Action method, this method allows for community empowerment, especially for Posbindu-PTM cadres. The participants of this service activity were 24 cadres of Posbindu-PTM in Sumberwono Village, 1 Ponkesdes nurse, and 1 village midwife. The form of activity includes counseling and practice in implementing Posbindu-PTM by implementing health protocols. This series of activities was carried out for 1 week and the result was an increase in the knowledge and skills of cadres regarding the implementation of Posbindu-PTM by implementing health protocols during the COVID-19 pandemic